(untitled) (Journal of Partial Differential Equations, 2018)
In this paper,we study the regularity of weak solutions to the 3D Micropolar-fluid equations. We show that the weak solutions actually is strong solution if the corresponding vorticity field j= abla× u satisfies certain condition in the high vorticity region.